Knowledge, Attitude and Use of Contraceptives Among Women of Reproductive Age in a Nigerian Rural Community - Monica Anurika Gbuchie; Ese Edirin Enughwure; Faithful Miebaka Daniel; Buokuromu Churson Obosi; Victoria Ezinne Emeruwa (International Journal of Medical Students, 2023)
BACKGROUND: The use of contraception, encompassing various methods such as hormonal pills, condoms, intrauterine devices, and natural techniques like abstinence, plays a pivotal role in family planning and reproductive health. Despite its importance, the utilization of contraceptives, particularly in low-resource nations like Nigeria, has remained notably low. This is concerning, considering the positive impact of contraception on maternal and child health and its contribution to national development by curbing population growth. In Nigeria, awareness of contraception is relatively high, but the adoption of modern contraceptive methods is alarmingly low, with only 10% of females utilizing them. This rate is notably insufficient given the high levels of sexual activity, especially among adolescents and young adults. Furthermore, regional disparities exist within Nigeria, with the south-south geopolitical zone exhibiting a higher prevalence of modern contraceptive use at 15.5%. Factors influencing contraceptive usage include education, religious beliefs, and awareness of available methods. In Yenagoa, Bayelsa state, the prevalence of modern contraceptives was notably higher at 36.8% in 2017, underscoring the impact of education and knowledge of contraceptive options. Increasing contraceptive use is crucial for Nigeria, a lower-middle-income country, as it not only aids in averting unplanned pregnancies and maternal mortality but also in controlling population growth.